On Broadway [videorecording (DVD)] - Jacoby, Oren; Jacoby, Oren; Baldwin, Alec, 1958-; Baranski, Christine; Lithgow, John, 1945- (Kino Lorber, 2021)
A behind-the-scenes look into the world of Broadway, its downfalls and comebacks, its new attention to inclusion, and a balance between art and commerce.